Privatisation of Urban and Regional Development: Achieving Societal Benefits or Business Objectives? Corporate Spatial Responsibility or Corporate Spatial Strategy? - Knieling, Jörg; Othengrafen, Frank; Preising, Tobias (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
Enterprises and business associations increasingly influence spatial development policies, being a public task in the first place. They develop own plans and positioning strategies, they contribute actively to political decision-making processes or they determine social norms and values. The production of space and place by private actors is not a new phenomenon. What is different, however, is that strategic entrepreneurial decisions are not only focusing on issues which are directly related to the enterprise’s divisions but encompassing urban or city-regional contexts as well as issues that could not directly be linked to a corporate’s business. This article presents selected case studies to analyse the rationales of enterprises, operating at supraregional level, with regard to their (spatial) involvement in local or regional contexts: Do private sector initiated development processes follow business-driven motivations or do enterprises altruistically assume responsibility for the local or regional place? Does this, according to the concept of Corporate Social Responsibility, even allow for speaking of a Corporate Spatial Responsibility? The qualities and spatial implications of the various business-driven strategic approaches will be systemised and evaluated by means of an analytical matrix. It becomes obvious that the entrepreneurial agenda, compared to the public agenda, is not that integrative. Enterprises only pursue social and spatial approaches, if those are not contradicting corporate goals and if they increase the operating income or improve the corporate’s image.
Keywords: urban development; regional development; entrepreneurial development strategies; corporate social responsibility; Place making